2010
DOI: 10.1021/pr9011574
|View full text |Cite
|
Sign up to set email alerts
|

A Proteomic View on the Role of Glucose in Peritoneal Dialysis

Abstract: Peritoneal dialysis is a frequently used mode of renal replacement therapy although peritoneal dialysis fluid (PDF) acts as stressor for mesothelial cells. In this study, stress response to PDF is investigated by a proteomics approach using Met-5A cell cultures closely resembling mesothelial cells. In a previous work, we identified about 100 proteins as significantly enhanced or diminished in abundance after full-PDF stress (90 mM glucose, pH 5.8, and presence of lactate and glucose degradation products (GDPs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 26 publications
2
18
0
Order By: Relevance
“…It has an established role in the enzymatic defence against protein and nucleotide glycation by dicarbonyls [28] but transcriptional control of Glo1 by a stress responsive mechanism has not hitherto been disclosed. Induction of Glo1 expression has been found in cells exposed to metabolic and inflammatory stress in vitro and in vivo: glomerular cells challenged by increased MG formation in hyperglycaemia associated with diabetes [29], mesothelial cells challenged by MG and high glucose concentrations of clinical dialysis fluids [30], and inflammatory stress induced by amyloidosis of Alzheimer's disease [31] and overexpression of α-synuclein in an experimental model of Parkinson's disease [32]. In these cases of increased cell dysfunction and damage and physiological morbidity, Glo1 induction was insufficient to prevent increased protein damage by MG.…”
Section: Discussionmentioning
confidence: 99%
“…It has an established role in the enzymatic defence against protein and nucleotide glycation by dicarbonyls [28] but transcriptional control of Glo1 by a stress responsive mechanism has not hitherto been disclosed. Induction of Glo1 expression has been found in cells exposed to metabolic and inflammatory stress in vitro and in vivo: glomerular cells challenged by increased MG formation in hyperglycaemia associated with diabetes [29], mesothelial cells challenged by MG and high glucose concentrations of clinical dialysis fluids [30], and inflammatory stress induced by amyloidosis of Alzheimer's disease [31] and overexpression of α-synuclein in an experimental model of Parkinson's disease [32]. In these cases of increased cell dysfunction and damage and physiological morbidity, Glo1 induction was insufficient to prevent increased protein damage by MG.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have searched for biomarkers in PDE correlating with PM function, detection of fibrosis, and/or the failure of the technique (reviewed in[25]). Proteomic studies of mesothelial cell lines[7] and transcriptome analysis in rats[26] have reported differences between the protein and miRNA content, respectively, of cells exposed or non-exposed to peritoneal liquids.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, peritoneal dialysis effluent is considered as a significant stressor for the MC layer (Breborowicz et al 1995;Wieslander et al 1991). To address this issue, a cell line derived from the MC layers was used as a model to study the glucoserelated pathways induced by high concentration of glucose (Lechner et al 2010). Using twodimensional fluorescence-difference gel electrophoresis (DIGE), altered proteins upon glucose stress in Met-5A cell were revealed.…”
Section: The Role Of Glucose In Peritoneal Dialysismentioning
confidence: 99%
“…Protein isoforms are distinguished by numbers in brackets. [Adapted from (Lechner et al 2010)] Another laboratory works on analyzing the protein composition of peritoneal fluid from patients receiving peritoneal dialysis with different concentration of glucose (Cuccurullo et al 2010). Peritoneal dialysis effluent with different glucose concentrations were revealed by 2DE.…”
Section: The Role Of Glucose In Peritoneal Dialysismentioning
confidence: 99%